A Double-Blinded Randomized Study Investigating a Possible Anti-Inflammatory Effect of Saxagliptin versus Placebo as Add-On Therapy in Patients with Both Type 2 Diabetes And Stable Coronary Artery Disease. (15th May 2017) - Njerve, Ida Unhammer; Åkra, Sissel; Weiss, Thomas W.; Solheim, Svein; Øvstebø, Reidun; Aass, Hans Christian D.; Byrkjeland, Rune; Arnesen, Harald; Seljeflot, Ingebjørg
Abstract : Background . Promising results regarding potential anti-inflammatory and antiatherosclerotic effects of gliptins have been reported. Our aim was to investigate whether saxagliptin treatment modifies expression of inflammatory markers, primarily in peripheral blood mononuclear cells (PBMCs) and in circulating leukocytes in patients with stable coronary artery disease (CAD) and T2DM. Methods . Patients (n = 12 ) were randomized to saxagliptin 5 mg daily or placebo for 3 months. Samples were taken at baseline and end of study in fasting state prior to intake of medications. PBMCs were isolated and cryopreserved at −150°C until ex vivo exposed to 1 ng/mL of lipopolysaccharide (LPS) for 4 hours. Gene expression was performed with custom-designed TaqMan® Arrays and relative quantification by real-time PCR (RT-qPCR). Results . HbA1c was reduced in the saxagliptin-treated group compared to that in the change with placebo (p = 0.042 ). In unstimulated PBMCs and in circulating leukocytes, we observed a significant increase in IL-10 expression in the saxagliptin group (p = 0.043, both), significantly different from that in the placebo (p = 0.009 and p = 0.032, resp.). No between group differences in changes were observed in any of the selected proinflammatory markers. Conclusion . In our small cohort of patients with combined T2DM and CAD, a possible anti-inflammatory effect of saxagliptin, observed in the present study by upregulation of IL-10 in leukocytes, needs to be confirmed in larger studies.